Factors to consider in the safe design of intensive care units – Part 1: historical aspects and ventilation systems. Issue 2 (March 2023) - Inkster, Teresa; Weinbren, Michael; Walker, Jimmy
Background: Evidence linking the role of ventilation systems in transmission of infection to patients in intensive care units has increased in recent years. Aims: This research-based commentary set out to identify the historical aspect of intensive care unit design, current problems and some potential solutions with respect to ventilation systems. Methods: Databases and open source information was used to obtain data on the historical aspects and current guidance in ICU, and the authors experiences have been used to suggest potential solutions to ventilation problems in ICU. Findings: The authors found a number of problems with ventilation in ICU to which there has not been a cohesive response in terms of guidance to support users and designers. The resultant void permits new projects to proceed with suboptimal and designs which place patients and staff at risk. Discussion: The NHS is now at the start of major new investments in healthcare facilities in England and this together with the end of the antibiotic era mandates new guidance to address these major concerns.